Video game consumer profiles - Tolić, Ivan, inženjer prometa (Array, 2020)
The video game development path is full of drastic changes. The growth and strengthening of technology and the growth of innovation in the technology sector have inevitably led to the growth of this industry, which is nowadays achieving unexpected, enviable results. The basic human need for entertainment and socializing contributes to the popularity of video games. Today, video games are played by people of all ages and genders, and the most common reasons for playing video games are fun, socializing, learning, and reducing stress, but video games also provide interactive entertainment, unlike books, movies or theatre performances. The popularity of video games is witnessed by numerous communities on social networks through which professional gamers share their experiences, tips and video game reviews, and there are statistics that support this popularity and growth. The features offered by the video game industry do not need to be particularly emphasized because the results, statistics and enthusiastic players speak for themselves. This paper deals with the demographics and behaviour of consumers playing video games. The aim is to identify the main features of the user, video game players, and to identify and determine user habits and trends affecting the users. The consumer is a social and cultural being. At the same time, he is an individual for himself, a member of a family, a member of a group or a certain class or class in society, a representative of a particular nation, race, religion, nationality of a particular country, etc. The consumer is a person who has the money (assets) and a will to buy the goods or a service. In this paper, the above consumer definitions will be brought in correlation with the video game market, with an industry that encompasses various forms of modern entertainment. It is shown that technology and new modes of entertainment are present among all, and that we need to adjust the time we live in.